Queer lives : men's autobiographies from nineteenth-century France - Peniston, William A., 1959-; Erber, Nancy, 1951- (University of Nebraska Press, 2007)
Gives readers a glimpse into the otherwise shrouded existences of gay men in nineteenth-century France. This work relates the experiences of a man about town, a cross-dressing entertainer, a troubled adolescent, and two fetishists, among others.